Association between Plasma FGF21 Levels and Body Composition in Patients with Gastric Cancer. (13th December 2022) - Zhang, Yingjing; Jiang, Lin; Su, Pengfei; Ma, Zhiqiang; Kang, Weiming; Ye, Xin; Liu, Yuqin; Yu, Jianchun
Abstract: Background: Accumulating evidence has suggested that Fibroblast growth factor 21 (FGF21) plays an important role in metabolic diseases. This study aimed to investigate the relationship between plasma FGF21 levels and body composition parameters in gastric cancer (GC) patients. Methods: This study was cross-sectional based on a prospective cohort of GC patients in a single center. Computer tomography (CT) and bioelectrical impedance analysis (BIA) were used to estimate skeletal muscle and adipose tissue mass. Blood samples were collected and plasma concentrations of FGF21 were measured by ELISA. Spearman's rank correlation test and logistic regression analysis were performed to assess associations between plasma FGF21 levels and these body composition parameters. Results: A total of 66 GC patients were enrolled in this study. Plasma FGF21 levels were significantly higher in women compared with men. The plasma FGF21 levels were positively correlated with fat mass index (FMI), fat mass percentage (FM%), and subcutaneous adipose tissue index (SATI). Furthermore, after adjustment for confounders, the lower plasma FGF21 levels were remain associated with increased odds for low SATI. Conclusions: Plasma FGF21 levels were positively associated with FMI, FM%, and SATI in GC patients, suggesting a potential mechanistic link between FGF21 and subcutaneous adipose tissue in GC.